Hadith #2193 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù ÙØÙØ¯ Ø§ÙØ¯Ø±Ø§ÙØ±Ø¯Ù; Abdullah bin Muslima al-Qa'nabi Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØ³ÙÙØ© Ø¨Ù ÙØ¹ÙØ¨ Ø§ÙÙØ¹ÙØ¨Ù; Abu Hurairah; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø (Sunan Abi Dawud)
I went out with Adi ibn Adi al-Kindi till we came to Mecca. He sent me to Safiyyah daughter of Shaybah who remembered a tradition (that she had heard) from Aisha. She said: I heard Aisha say: I heard the Messenger of Allah (ï·º) say: There is no divorce or emancipation in case of constraint or duress (ghalaq). Abu Dawud said: I think ghalaq means anger.
Grade: Hasan

Hadith #2217 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ±Ù Ø§ÙØ£ÙØ²Ø§Ø¹Ù; Abu Da'ud Ø£Ø¨Ù Ø¯Ø§ÙØ¯ Ø§ÙØ³Ø¬Ø³ØªØ§ÙÙ Ø§ÙØ£Ø²Ø¯Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Bashr bin Bakr al-Tunisi Ø¨Ø´Ø± Ø¨Ù Ø¨ÙØ± Ø§ÙØªÙÙØ³Ù (Sunan Abi Dawud)
The tradition mentioned above has been transmitted by Sulaiman bin Yasar. This version has âThen some dates were brought to the Apostle of Allaah(ï·º) and he gave it him. They measured about fifteen saâs â. He said âGive them in almsâ. He said âIs there anyone needier than I and my family. Apostle of Allaah(ï·º)?â The Apostle of Allaah(ï·º) said âEat them, you and your family.â
Grade: Hasan

Hadith #2300 - Sunan Abi Dawud - Abdullah bin Abi Najih Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù ÙØ¬ÙØ; Abu Hudhayfa al-Nahdi ÙÙØ³Ù Ø¨Ù ÙØ³Ø¹ÙØ¯ Ø£Ø¨Ù ØØ°ÙÙØ© Ø§ÙÙÙØ¯Ù; Ahmed bin Muhammad bin Musa al-Samsar Ø£ØÙØ¯ Ø¨Ù ÙØÙØ¯ Ø¨Ù ÙÙØ³Ù Ø§ÙØ³ÙØ³Ø§Ø±; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Shabl bin 'Aabad al-Makki Ø´Ø¨Ù Ø¨Ù Ø¹Ø¨Ø§Ø¯ Ø§ÙÙÙÙ (Sunan Abi Dawud)
âShould I return to my people, for he did not leave any dwelling house of his own and maintenance for me? She said: The Messenger of Allah (ï·º) replied: Yes. She said: I came out, and when I was in the apartment or in the mosque, he called for me, or he commanded (someone to call me) and, therefore, I was called. He said: what did you say? So I repeated my story which I had already mentioned about my husband. Thereupon he said: Stay in your house till the term lapses. She said: So I passed my
Grade: Sahih

Hadith #2806 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù Ø³ÙÙØ¯ Ø§ÙÙØ¨Ø·Ù; Ahmad bin Hanbal Ø£ØÙØ¯ Ø¨Ù ØÙØ¨Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Hashaym bin Bashayr bin al-Qasim ÙØ´ÙÙ Ø¨Ù Ø¨Ø´ÙØ± Ø¨Ù Ø§ÙÙØ§Ø³Ù; Jabir ibn 'Abdullah (Sunan Abi Dawud)
I asked Saâid b. al-Musayyab: What is meant by animal with a slit ear and broken horn ? He replied: Half and more than half.
Grade: Sahih

Hadith #2807 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Hammad bin Zayd ØÙØ§Ø¯ Ø¨Ù Ø²ÙØ¯ Ø¨Ù Ø¯Ø±ÙÙ Ø§ÙØ£Ø²Ø¯Ù Ø§ÙØ£Ø²Ø±Ù; Jabir ibn 'Abdullah; Musa bin Isma'il al-Munqari al-Tabudhaki ÙÙØ³Ù Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ Ø§ÙÙÙÙØ±Ù - ÙØªØ¨ÙØ°ÙÙ; Qays bin Abi Hazim ÙÙØ³ Ø¨Ù Ø£Ø¨Ù ØØ§Ø²Ù (Sunan Abi Dawud)
We performed tamattuâ during the lifetime of the Messenger of Allah (ï·º), sacrificed a cow for seven and a camel for seven people. We shared them.
Grade: Sahih

Hadith #2833 - Sunan Abi Dawud - Amr bin Dinar Ø¹ÙØ±Ù Ø¨Ù Ø¯ÙÙØ§Ø± Ø§ÙØ£Ø«Ø±Ù Ø§ÙØ¬ÙØÙ; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Masdad bin Masrhad ÙØ³Ø¯Ø¯ Ø¨Ù ÙØ³Ø±ÙØ¯ Ø¨Ù ÙØ³Ø±Ø¨Ù; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Umm Kurz al-Khuza'iyya (Sunan Abi Dawud)
The Messenger of Allah (ï·º) used to sacrifice goat out of every fifty goats. Abu Dawud said: Faraâ means the first baby camel born (to the Arabs). They used to sacrifice it for their idols, and then eat it, and its skin was thrown on a tree. âAtira was a sacrifice made during the first ten days of Rajab.
Grade: Sahih

Hadith #2870 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; ibn Abbas; Jarir bin 'Abdul Hameed al-Razi Ø¬Ø±ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØÙÙØ¯ Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¶Ø¨Ù; Sa'id bin Jubayr Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬Ø¨ÙØ± Ø§ÙØ£Ø³Ø¯Ù; Uthman bin Muhammad (Sunan Abi Dawud)
I heard the Messenger of Allah (ï·º) say: Allah has appointed for everyone who has a right what is due to him, and no bequest must be made to an heir.
Grade: Sahih

Hadith #3047 - Sunan Abi Dawud - Abdur Rahman bin Mahdi Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù ÙÙØ¯Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Muhammad bin Bashar Bindar ÙØÙØ¯ Ø¨Ù Ø¨Ø´Ø§Ø± Ø¨ÙØ¯Ø§Ø±; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Harb bin âUbaid Allah from the Prophet (ï·º) to the same effect through a different chain of narrators. This version has the word kharaj(land tax) instead of âushr (tithes).
Grade: Da'if

Hadith #3304 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Habib al-Ma'lm Abu Muhammad ØØ¨ÙØ¨ Ø§ÙÙØ¹ÙÙ Ø£Ø¨Ù ÙØÙØ¯ Ø§ÙØ¨ØµØ±Ù; Hammad bin Zayd ØÙØ§Ø¯ Ø¨Ù Ø²ÙØ¯ Ø¨Ù Ø¯Ø±ÙÙ Ø§ÙØ£Ø²Ø¯Ù Ø§ÙØ£Ø²Ø±Ù; Musa bin Isma'il al-Munqari al-Tabudhaki ÙÙØ³Ù Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ Ø§ÙÙÙÙØ±Ù - ÙØªØ¨ÙØ°ÙÙ (Sunan Abi Dawud)
Uqbah said to the Prophet (ï·º): My sister has taken a vow that she will walk to the House of Allah (the Kaâbah). Thereupon he said: Allah will not do anything of the walking of your sister to the House of Allah (i.e. the Kaâbah).
Grade: Sahih

Hadith #3372 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Jabir ibn 'Abdullah; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù (Sunan Abi Dawud)
I asked Abu Zinad about the sale of fruits before they were clearly in good condition, and what was said about it. He replied: Urwah ibn az-Zubayr reports a tradition from Sahl ibn Abi Hathmah on the authority of Zayd ibn Thabit who said: The people used to sell fruits before they were clearly in good condition. When the people cut off the fruits, and were demanded to pay the price, the buyer said: The fruits have been smitten by duman, qusham and murad fruit diseases on which they used to dispu
Grade: Sahih

Hadith #3402 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' Ø£Ø¨Ù Ø¥Ø³ØØ§Ù Ø§ÙØ³Ø¨ÙØ¹Ù Ø¹ÙØ±Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ; Rafi' bin Khadij bin Rafi'; Sharayk bin 'Abdullah Ø´Ø±ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ®Ø¹Ù (Sunan Abi Dawud)
Rafiâ had cultivated a land. The Prophet (ï·º) passed him when he was watering it. So he asked him: To whom does the crop belong, and to whom does the land belong? He replied: The crop is mine for my seed and labour. The half (of the crop) is mine and the half for so-and-so. He said: You conducted usurious transaction. Return the land to its owner and take your wages and cost.
Grade: Da'if

Hadith #3404 - Sunan Abi Dawud - Aabad bin al-Wam bin Ø¹Ø¨Ø§Ø¯ Ø¨Ù Ø§ÙØ¹ÙØ§Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Jabir ibn 'Abdullah; Sufyan bin Hussain bin al-Hasan Ø³ÙÙØ§Ù Ø¨Ù ØØ³ÙÙ Ø§ÙØ³ÙÙÙ; Yonus bin 'Ubaid bin Dinar ÙÙÙØ³ Ø¨Ù Ø¹Ø¨ÙØ¯ Ø¨Ù Ø¯ÙÙØ§Ø± Ø§ÙØ¹Ø¨Ø¯Ù (Sunan Abi Dawud)
The Messenger of Allah (ï·º) forbade muhaqalah, muzabanah, mukhabarah, and muâawanah. One of the two narrators from Hammad said the word muâawamah, and other said: âselling many years aheadâ. The agreed version then goes: and thunya, but gave license for âaraya.
Grade: Sahih

Hadith #3470 - Sunan Abi Dawud - Abdullah bin Wahb Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙÙØ¨ Ø¨Ù ÙØ³ÙÙ Ø§ÙÙØ±Ø´Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Sulaiman bin Da'ud bin Da'ud Ø³ÙÙÙØ§Ù Ø¨Ù Ø¯Ø§ÙØ¯ Ø¨Ù Ø¯Ø§ÙØ¯ Ø¨Ù Ø¹ÙÙ (Sunan Abi Dawud)
The Messenger of Allah (ï·º) as saying: If you were to sell dried dates to your brother and they were smitten by blight, it will not be allowable for you to take your brotherâs property unjustly.
Grade: Sahih

Hadith #3485 - Sunan Abi Dawud - al-Laith bin Sa'd Ø§ÙÙÙØ« Ø¨Ù Ø³Ø¹Ø¯; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Jabir ibn 'Abdullah; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ; Yazid bin Abi Habib ÙØ²ÙØ¯ Ø¨Ù Ø£Ø¨Ù ØØ¨ÙØ¨ (Sunan Abi Dawud)
The Messenger of Allah (ï·º) as saying: Allah forbade wine and the price paid for it, and forbade dead meat and the price paid for it, and forbade swine and the price paid for it.
Grade: Sahih

Hadith #3517 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù Ø³ÙÙØ¯ Ø§ÙÙØ¨Ø·Ù; Ahmad bin Hanbal Ø£ØÙØ¯ Ø¨Ù ØÙØ¨Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Hashaym bin Bashayr bin al-Qasim ÙØ´ÙÙ Ø¨Ù Ø¨Ø´ÙØ± Ø¨Ù Ø§ÙÙØ§Ø³Ù; Jabir ibn 'Abdullah (Sunan Abi Dawud)
The Prophet (ï·º) said: A neighbour has the best claim to the house or land of the neighbour.
Grade: Sahih

Hadith #3555 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Jabir ibn 'Abdullah; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù (Sunan Abi Dawud)
The life-tenancy which the Messenger of Allah (ï·º) allowed was only that one should say: It is for you and your descendants. When he says: It is yours as long as you live, it returns to its owner.
Grade: Sahih

Hadith #3563 - Sunan Abi Dawud - Abdul 'Aziz bin Rafi' Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø±ÙÙØ¹; Abu al-Ahwus, Salam bin Sulaym al-Hanafi Ø£Ø¨Ù Ø§ÙØ£ØÙØµ Ø³ÙØ§Ù Ø¨Ù Ø³ÙÙÙ Ø§ÙØÙÙÙ; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Masdad bin Masrhad ÙØ³Ø¯Ø¯ Ø¨Ù ÙØ³Ø±ÙØ¯ Ø¨Ù ÙØ³Ø±Ø¨Ù (Sunan Abi Dawud)
AbdulAziz ibn Rufayâ narrated on the authority of some people from the descendants of Abdullah ibn Safwan who reported the Messenger of Allah (ï·º) as saying: Have you weapons, Safwan? He asked: On loan or by force? He replied: No, but on loan. So he lent him coats of mail numbering between thirty and forty! The Messenger of Allah (ï·º) fought the battle of Hunayn. When the polytheists were defeated, the coats of mail of Safwan were collected. Some of them were lost. The Messenger of Allah (ï·
Grade: Sahih

Hadith #3565 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Hiban bin Hilal ØØ¨Ø§Ù Ø¨Ù ÙÙØ§Ù; Hmam bin Yahya bin Dinar ÙÙØ§Ù Ø¨Ù ÙØÙÙ Ø¨Ù Ø¯ÙÙØ§Ø±; Qatada ÙØªØ§Ø¯Ø©; Safwan bin Y'ala bin Umayya ØµÙÙØ§Ù Ø¨Ù ÙØ¹ÙÙ Ø¨Ù Ø£ÙÙØ©; Ya'la bin Umayya (Sunan Abi Dawud)
I heard the Messenger of Allah (ï·º) Said: Allah , Most Exalted, has appointed for everyone who has a right what is due to him, and no will be made to an heir, and a woman should not spend anything from her house except with the permission of her husband. He was asked: Even foodgrain, Messenger of Allah? He replied: That is the best of our property. He then said: A loan must be paid back, a she-camel lent for a time for milking must be returned, a debt must be discharged, one who stands surety i
Grade: Sahih

Hadith #3657 - Sunan Abi Dawud - Abu Hurairah; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Hammad bin Zayd ØÙØ§Ø¯ Ø¨Ù Ø²ÙØ¯ Ø¨Ù Ø¯Ø±ÙÙ Ø§ÙØ£Ø²Ø¯Ù Ø§ÙØ£Ø²Ø±Ù; Musa bin Isma'il al-Munqari al-Tabudhaki ÙÙØ³Ù Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ Ø§ÙÙÙÙØ±Ù - ÙØªØ¨ÙØ°ÙÙ (Sunan Abi Dawud)
The Prophet (ï·º) said: If anyone is given a legal decision ignorantly, the sin rests on the one who gave it. Sulayman al-Mahri added in his version: If anyone advises his brother, knowing that guidance lies in another direction, he has deceived him. These are the wordings of Sulayman.
Grade: Hasan

Hadith #3702 - Sunan Abi Dawud - al-Laith bin Sa'd Ø§ÙÙÙØ« Ø¨Ù Ø³Ø¹Ø¯; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Jabir ibn 'Abdullah; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ (Sunan Abi Dawud)
Dates were steeped for the Messenger of Allah (ï·º) in a skin, but when they could not find a skin, they were steeped for him in a small stone vessel.
Grade: Sahih

Hadith #3713 - Sunan Abi Dawud - Ahmad bin Hanbal Ø£ØÙØ¯ Ø¨Ù ØÙØ¨Ù; Aisha bint Abi Bakr; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Hajjaj bin Muhammad al-Musaysi ØØ¬Ø§Ø¬ Ø¨Ù ÙØÙØ¯ Ø§ÙÙØµÙØµÙ Ø§ÙØ£Ø¹ÙØ±; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Ubaid bin 'Umayr bin Qatada Ø¹Ø¨ÙØ¯ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù ÙØªØ§Ø¯Ø© (Sunan Abi Dawud)
Raisins were steeped for the Prophet (ï·º) and he would drink it in the morning and the night after, the following day and the night after. He then gave orders and it was given to servants to drinks or poured away. Abu Dawud said: That âit was given to servants to drinkâ means before it spoiled. Abu Dawud said: Abu âUmar Yahya al-Bahrani.
Grade: Sahih

Hadith #3730 - Sunan Abi Dawud - Ahmad bin Hanbal Ø£ØÙØ¯ Ø¨Ù ØÙØ¨Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Jabir ibn 'Abdullah; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan Abi Dawud)
I was in the house of Maymunah. The Messenger of Allah (ï·º) accompanied by Khalid ibn al-Walid entered. Two roasted long-tailed lizards (dabb) placed on the sticks were brought to him. The Messenger of Allah (ï·º) spat. Khalid said: I think that you abominate it, Messenger of Allah. He said: Yes. Then the Messenger of Allah (ï·º) was brought milk, and he drank (it). The Messenger of Allah (ï·º) then said: When one of you eats food, he should say: O Allah, bless us in it, and give us food (or no
Grade: Hasan

Hadith #3732 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Hammad bin Zayd ØÙØ§Ø¯ Ø¨Ù Ø²ÙØ¯ Ø¨Ù Ø¯Ø±ÙÙ Ø§ÙØ£Ø²Ø¯Ù Ø§ÙØ£Ø²Ø±Ù; Kathir bin Shanzayr ÙØ«ÙØ± Ø¨Ù Ø´ÙØ¸ÙØ±; Masdad bin Masrhad ÙØ³Ø¯Ø¯ Ø¨Ù ÙØ³Ø±ÙØ¯ Ø¨Ù ÙØ³Ø±Ø¨Ù (Sunan Abi Dawud)
Jabir b.âAbd Allah reported the Prophet (ï·º)as saying this version is not complete ââfor the devil does not open a shut door, or loosen a water-skin, or uncover a vessel, for a mouse sets a house on fire over its inhabitantsââ.
Grade: Sahih

Hadith #3821 - Sunan Abi Dawud - Abdullah bin Wahb Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙÙØ¨ Ø¨Ù ÙØ³ÙÙ Ø§ÙÙØ±Ø´Ù; Ahmed bin Salah al-Masri Ø£ØÙØ¯ Ø¨Ù ØµØ§ÙØ Ø§ÙÙØµØ±Ù; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Jabir ibn 'Abdullah; Yonus bin Yazid bin Abi al-Nijad ÙÙÙØ³ Ø¨Ù ÙØ²ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø§ÙÙØ¬Ø§Ø¯ (Sunan Abi Dawud)
What a good condiment vinegar is!
Grade: Sahih

Hadith #3837 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø§ÙØ¨ØµØ±Ù Ø§ÙØ³Ø§ÙÙ; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Bard bin Sinan Ø¨Ø±Ø¯ Ø¨Ù Ø³ÙØ§Ù; Jabir ibn 'Abdullah; Uthman bin Muhammad (Sunan Abi Dawud)
The Messenger of Allah (ï·º) came to visit us and we offered him butter and dates, for he liked butter and dates.
Grade: Sahih

Hadith #3846 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; ibn Abbas; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Masdad bin Masrhad ÙØ³Ø¯Ø¯ Ø¨Ù ÙØ³Ø±ÙØ¯ Ø¨Ù ÙØ³Ø±Ø¨Ù; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan Abi Dawud)
If the servant of any of you prepares food for him, and he brings it to him, while he had suffered its heat and smoke. He should make him sit with him to eat. If the food is scanty, he should put one or two morsels in his hand.
Grade: Sahih

Hadith #3917 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil Ø§ÙØ¶ØØ§Ù Ø¨Ù ÙØ®ÙØ¯ Ø£Ø¨Ù Ø¹Ø§ØµÙ Ø§ÙÙØ¨ÙÙ; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Yahya bin Khlf al-Bahly ÙØÙÙ Ø¨Ù Ø®ÙÙ Ø§ÙØ¨Ø§ÙÙÙ Ø£Ø¨Ù Ø³ÙÙØ© Ø§ÙØ¨ØµØ±Ù (Sunan Abi Dawud)
When the Messenger of Allah (ï·º) heard a word, and he liked it, he said: We took your omen from your mouth.
Grade: Sahih

Hadith #3953 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Hammad bin Zayd ØÙØ§Ø¯ Ø¨Ù Ø²ÙØ¯ Ø¨Ù Ø¯Ø±ÙÙ Ø§ÙØ£Ø²Ø¯Ù Ø§ÙØ£Ø²Ø±Ù; Jabir ibn 'Abdullah; Musa bin Isma'il al-Munqari al-Tabudhaki ÙÙØ³Ù Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ Ø§ÙÙÙÙØ±Ù - ÙØªØ¨ÙØ°ÙÙ; Qays bin Abi Hazim ÙÙØ³ Ø¨Ù Ø£Ø¨Ù ØØ§Ø²Ù (Sunan Abi Dawud)
My uncle brought me (to Medina) in the pre-Islamic days. He sold me to al-Hubab ibn Amr, brother of AbulYusr ibn Amr. I bore a child, AbdurRahman ibn al-Hubab, to him and he (al-Hubab) then died. Thereupon his wife said: I swear by Allah, now you will be sold (as a repayment) for his loan. So I came to the Messenger of Allah (ï·º) and said: Messenger of Allah! I am a woman of Banu Kharijah Qays ibn Aylan. My uncle had brought me to Medina in pre-Islamic days. He sold me to al-Hubab ibn Amr, brot
Grade: Da'if

Hadith #3954 - Sunan Abi Dawud - Abdul Malik bin Aby Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø³ÙÙÙØ§Ù; Ahmad bin Hanbal Ø£ØÙØ¯ Ø¨Ù ØÙØ¨Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Hashaym bin Bashayr bin al-Qasim ÙØ´ÙÙ Ø¨Ù Ø¨Ø´ÙØ± Ø¨Ù Ø§ÙÙØ§Ø³Ù; Isma'il bin Abi Khalid al-Ahmsi Ø¥Ø³ÙØ§Ø¹ÙÙ Ø¨Ù Ø£Ø¨Ù Ø®Ø§ÙØ¯ Ø§ÙØ£ØÙØ³Ù; Jabir ibn 'Abdullah; Salmah bin Kahayl al-Hadrami Ø³ÙÙØ© Ø¨Ù ÙÙÙÙ Ø¨Ù ØØµÙÙ (Sunan Abi Dawud)
We sold slave-mothers during the time of the Messenger of Allah (ï·º) and of AbuBakr. When Umar was in power, he forbade us and we stopped.
Grade: Sahih

Hadith #3955 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ±Ù Ø§ÙØ£ÙØ²Ø§Ø¹Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Bashr bin Bakr al-Tunisi Ø¨Ø´Ø± Ø¨Ù Ø¨ÙØ± Ø§ÙØªÙÙØ³Ù; Ja'far bin Msafr bin Rashid Ø¬Ø¹ÙØ± Ø¨Ù ÙØ³Ø§ÙØ± Ø¨Ù Ø±Ø§Ø´Ø¯; Jabir ibn 'Abdullah (Sunan Abi Dawud)
A man declared that his slave would be free after his death, but he had no other property. So the Prophet (ï·º) ordered (to sell him). He was then sold for seven hundred or nine hundred (dirhams).
Grade: Sahih

Hadith #3973 - Sunan Abi Dawud - Amr bin Dinar Ø¹ÙØ±Ù Ø¨Ù Ø¯ÙÙØ§Ø± Ø§ÙØ£Ø«Ø±Ù Ø§ÙØ¬ÙØÙ; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; ibn Abbas; Muhammad bin 'Isa bin Hyan ÙØÙØ¯ Ø¨Ù Ø¹ÙØ³Ù Ø¨Ù ØÙØ§Ù; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù (Sunan Abi Dawud)
I came in the deputation of Banu al-Muntafiq to the Messenger of Allah (ï·º). He then narrated the rest of the tradition. The Prophet (ï·º) said: la tahsibanna (do not think) and did not say: la tahsabanna (do not think).
Grade: Sahih

Hadith #3991 - Sunan Abi Dawud - Ahmad bin Hanbal Ø£ØÙØ¯ Ø¨Ù ØÙØ¨Ù; Ahmed bin 'Ubda bin Musa Ø£ØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯Ø© Ø¨Ù ÙÙØ³Ù; Amr bin Dinar Ø¹ÙØ±Ù Ø¨Ù Ø¯ÙÙØ§Ø± Ø§ÙØ£Ø«Ø±Ù Ø§ÙØ¬ÙØÙ; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Safwan bin 'Amr bin Harm al-Saksaki ØµÙÙØ§Ù Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ÙØ±Ù Ø§ÙØ³ÙØ³ÙÙ; Sufyan bin 'Uyaynah Ø³ÙÙØ§Ù Ø¨Ù Ø¹ÙÙÙØ© (Sunan Abi Dawud)
I heard the Messenger of Allah (ï·º) read: â(There is for him) Rest and satisfactionâ (faruhun wa rayhan).
Grade: Hasan

Hadith #4011 - Sunan Abi Dawud - Abdul Malik bin Aby Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø³ÙÙÙØ§Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Ya'la bin 'Ubaid bin Umayya al-Tanafasi ÙØ¹ÙÙ Ø¨Ù Ø¹Ø¨ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø£ÙÙØ© Ø§ÙØ·ÙØ§ÙØ³Ù; Zuhayr bin Mua'wiya bin Hudayj Ø²ÙÙØ± Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø¨Ù ØØ¯ÙØ¬ (Sunan Abi Dawud)
The Prophet (ï·º) said: After some time the lands of the non-Arabs will be conquered for you, and there you will find houses called hammamat (hot baths). so men should not enter them (to wash) except in lower garments, and forbid the women to enter them except a sick or one who is in a child-bed.
Grade: Da'if

Hadith #4012 - Sunan Abi Dawud - Abdul Malik bin Aby Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø³ÙÙÙØ§Ù; Abu Bakr bin 'Ayyash al-Asadi Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø¹ÙØ§Ø´ Ø¨Ù Ø³Ø§ÙÙ Ø§ÙØ£Ø³Ø¯Ù; al-'Aswad bin 'Amir Shadhan Ø§ÙØ£Ø³ÙØ¯ Ø¨Ù Ø¹Ø§ÙØ± Ø´Ø§Ø°Ø§Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Muhammad bin Ahmed bin Abi Khalaf ÙØÙØ¯ Ø¨Ù Ø£ØÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø®ÙÙ; Safwan bin Y'ala bin Umayya ØµÙÙØ§Ù Ø¨Ù ÙØ¹ÙÙ Ø¨Ù Ø£ÙÙØ©; Ya'la bin Umayya (Sunan Abi Dawud)
The Messenger of Allah (ï·º) saw a man washing in a public place without a lower garment. So he mounted the pulpit, praised and extolled Allah and said: Allah is characterised by modesty and concealment. So when any of you washes, he should conceal himself.
Grade: Sahih

Hadith #4385 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Ayoub bin Musa bin 'Amr bin Sa'id Ø£ÙÙØ¨ Ø¨Ù ÙÙØ³Ù Ø¨Ù Ø¹ÙØ±Ù; ibn Abbas; Ibn Ishaq ÙØÙØ¯ Ø¨Ù Ø¥Ø³ØØ§Ù Ø¨Ù ÙØ³Ø§Ø±â; Muhammad bin 'Abdullah bin Numayr ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙÙÙØ±; Uthman bin Muhammad (Sunan Abi Dawud)
The Messenger of Allah (ï·º) had thiefâs hand cut off for a shield worth three dirhams.
Grade: Sahih

Hadith #4463 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi Ø£Ø¨Ù Ø§ÙØ£ØÙØµ Ø³ÙØ§Ù Ø¨Ù Ø³ÙÙÙ Ø§ÙØÙÙÙ; Asim al-Ahwal Ø¹Ø§ØµÙ Ø§ÙØ£ØÙÙ; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; ibn Abbas; Mas'ud bin Malik Abu Razayn al-Asadi ÙØ³Ø¹ÙØ¯ Ø¨Ù ÙØ§ÙÙ Ø£Ø¨Ù Ø±Ø²ÙÙ Ø§ÙØ£Ø³Ø¯Ù; Sharayk bin 'Abdullah Ø´Ø±ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙÙØ®Ø¹Ù (Sunan Abi Dawud)
If a man who is not married is seized committing sodomy, he will be stoned to death. Abu Dawud said: The tradition of âAsim proved the tradition of âAmir b. Abi âAmr as weak.
Grade: Hasan

Hadith #4541 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Hammad bin Zayd ØÙØ§Ø¯ Ø¨Ù Ø²ÙØ¯ Ø¨Ù Ø¯Ø±ÙÙ Ø§ÙØ£Ø²Ø¯Ù Ø§ÙØ£Ø²Ø±Ù; Ibn Ishaq ÙØÙØ¯ Ø¨Ù Ø¥Ø³ØØ§Ù Ø¨Ù ÙØ³Ø§Ø±â; Musa bin Isma'il al-Munqari al-Tabudhaki ÙÙØ³Ù Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ Ø§ÙÙÙÙØ±Ù - ÙØªØ¨ÙØ°ÙÙ (Sunan Abi Dawud)
On his fatherâs authority, said that his grandfather reported the Messenger of Allah (ï·º) gave judgment that if anyone is killed accidentally, his blood-wit should be one hundred camels: thirty she-camels which had entered their second year, thirty she-camels which had entered their third year, thirty she-camels which had entered their fourth year, and ten male camels which had entered their third year.
Grade: Hasan

Hadith #4542 - Sunan Abi Dawud - Abu Da'ud Ø£Ø¨Ù Ø¯Ø§ÙØ¯ Ø§ÙØ³Ø¬Ø³ØªØ§ÙÙ Ø§ÙØ£Ø²Ø¯Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Ibn Ishaq ÙØÙØ¯ Ø¨Ù Ø¥Ø³ØØ§Ù Ø¨Ù ÙØ³Ø§Ø±â; Jabir ibn 'Abdullah; Yahya bin Wadh ÙØÙÙ Ø¨Ù ÙØ§Ø¶Ø (Sunan Abi Dawud)
On his fatherâs authority, said that his grandfather reported that the value of the blood-money at the time of the Messenger of Allah (ï·º) was eight hundred dinars or eight thousand dirhams, and the blood-money for the people of the Book was half of that for Muslims. He said: This applied till Umar (Allah be pleased with him) became caliph and he made a speech in which he said: Take note! Camels have become dear. So Umar fixed the value for those who possessed gold at one thousand dinars, for
Grade: Hasan

Hadith #4582 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Masdad bin Masrhad ÙØ³Ø¯Ø¯ Ø¨Ù ÙØ³Ø±ÙØ¯ Ø¨Ù ÙØ³Ø±Ø¨Ù; Safwan bin Y'ala bin Umayya ØµÙÙØ§Ù Ø¨Ù ÙØ¹ÙÙ Ø¨Ù Ø£ÙÙØ©; Ya'la bin Umayya; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan Abi Dawud)
The Prophet (ï·º) said: When a mukatab (a slave who has made an agreement to purchase his freedom) gifts blood-money or an inheritance, he can inherit in accordance with the extent to which he has been emancipated. Abu Dawud said: Wuhaib transmitted it from Ayyub, from âIkrimah, on the authority of âAli, from the Prophet (ï·º): and Hammad b. Zaid and Ismaâil have transmitted it in a mursal form (i.e the link of the Companion being missing) from Ayyub, from âIkrimah, from the Prophet (ï·º
Grade: Sahih

Hadith #4583 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù Ø³ÙÙØ¯ Ø§ÙÙØ¨Ø·Ù; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Hajjaj bin al-Minhal ØØ¬Ø§Ø¬ Ø¨Ù Ø§ÙÙÙÙØ§Ù; Hashaym bin Bashayr bin al-Qasim ÙØ´ÙÙ Ø¨Ù Ø¨Ø´ÙØ± Ø¨Ù Ø§ÙÙØ§Ø³Ù; Ziyad bin Ayoub - Dulwiyya Ø²ÙØ§Ø¯ Ø¨Ù Ø£ÙÙØ¨ Ø¨Ù Ø²ÙØ§Ø¯ Ø¯ÙÙÙÙ (Sunan Abi Dawud)
On his fatherâs authority, said that his grandfather reported the Messenger of Allah (ï·º) said: The blood-wit for a man who makes a covenant is half of the blood-wit for a free man. Abu Dawud said: It has been transmitted by Usamah b. Zaid al-Laithi and âAbd al-Rahman b. al-Harith on the authority of âAmr b. Suhâaib in similar manner.
Grade: Hasan

Hadith #4898 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' ÙØÙØ¯ Ø¨Ù Ø§ÙØ¹ÙØ§Ø¡ - Ø£Ø¨Ù ÙØ±ÙØ¨; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; ibn Umar; Imran bin Anas Ø¹ÙØ±Ø§Ù Ø¨Ù Ø£ÙØ³; Mua'wiya bin Hisham al-Qsar ÙØ¹Ø§ÙÙØ© Ø¨Ù ÙØ´Ø§Ù Ø§ÙÙØµØ§Ø± (Sunan Abi Dawud)
Ibn Awn said: I asked about the meaning of intisar (revenge) in the Qurâanic verse: âBut indeed if any do help and defend themselves (intasara) after a wrong (done) to them, against them there is no cause of blame.â Then Ali ibn Zayd ibn Jadâan told me on the authority of Umm Muhammad, the wife of his father. Ibn Awn said: It was believed that she used to go to the Mother of the Faithful (i.e. Aisha). She said: The Mother of the Faithful said: The Messenger of Allah (ï·º) came upon me wh
Grade: Da'if

Hadith #4907 - Sunan Abi Dawud - Aisha bint Abi Bakr; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Habib al-Ma'lm Abu Muhammad ØØ¨ÙØ¨ Ø§ÙÙØ¹ÙÙ Ø£Ø¨Ù ÙØÙØ¯ Ø§ÙØ¨ØµØ±Ù; Mua'dh bin Mua'dh bin Nsr ÙØ¹Ø§Ø° Ø¨Ù ÙØ¹Ø§Ø° Ø¨Ù ÙØµØ±; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Ubaidullah bin Mua'dh Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù ÙØ¹Ø§Ø° Ø¨Ù ÙØ¹Ø§Ø° Ø¨Ù ÙØµØ± (Sunan Abi Dawud)
I heard the Messenger of Allah (May peace be upon him) say: Men given to cursing will not be witnesses or intercessors.
Grade: Sahih

Hadith #5180 - Sunan Abi Dawud - Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Ruh bin 'Ubada bin al-'Ala' Ø±ÙØ Ø¨Ù Ø¹Ø¨Ø§Ø¯Ø© Ø¨Ù Ø§ÙØ¹ÙØ§Ø¡; Ubaid bin 'Umayr bin Qatada Ø¹Ø¨ÙØ¯ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù ÙØªØ§Ø¯Ø©; Yahya bin Habib bin Arby ÙØÙÙ Ø¨Ù ØØ¨ÙØ¨ Ø¨Ù Ø¹Ø±Ø¨Ù (Sunan Abi Dawud)
I was sitting in one of the meeting of the Ansar. Abu Musa came terrified. We asked him; what makes you terrified? He replied: âUmar sent for me; so I went to him and asked his permission three times, but he did not permit me (to enter), so I came back. He asked; what has prevented you from coming to me? I replied: I came and asked permission three times, but it was not granted to me (so I returned). The Messenger of Allah (May peace be upon him) has said: When one of you asks permission three
Grade: Sahih

Hadith #5189 - Sunan Abi Dawud - Ahmed bin 'Amr bin al-Sarh Ø£ØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù Ø§ÙØ³Ø±Ø Ø£Ø¨Ù Ø§ÙØ·Ø§ÙØ±; Ata' bin Abi Rabah Ø¹Ø·Ø§Ø¡ Ø¨Ù Ø£Ø¨Ù Ø±Ø¨Ø§Ø; ibn Abbas; Sufyan bin 'Uyaynah Ø³ÙÙØ§Ù Ø¨Ù Ø¹ÙÙÙØ©; Ubaidullah bin Abi Yazid Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù ÙØ²ÙØ¯ Ø§ÙÙÙÙ (Sunan Abi Dawud)
The Prophet (ï·º) said: A manâs messenger sent to another indicates his permission to enter.
Grade: Sahih